CURRENT STATUS OF PHOTOVOLTAIC SOLAR SYSTEM IN INDIA: A Review - Shekhawat, Monika; Pareek, Smita (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Solar power is defined as the direct conversion of sunlight into form of electricity with the help of Photovoltaic (PV) or by Concentrated Solar Power (CSP).In PV, semiconducting material are used for converting the light into electricity having photovoltaic effect. Solar energy occurs in many forms like a solar photovoltaic, heat thermal and fuels which have a clean climate, protective, abundant and in-exhaustive energy resource for human beings .Many research for development of this energy has been done and many are undergoing because of the advantages that is offered by this technology. In this paper, we are trying to present the current status and future scope of solar photovoltaic energy system that will be helpful for both researchers and scientist in forecasting.